Efficacy of TNFα inhibitors for refractory vascular Behçet's disease: A multicenter observational study of 27 patients and a review of the literature. (24th January 2020) - Aksoy, Aysun; Yazici, Ayten; Omma, Ahmet; Cefle, Ayse; Onen, Fatos; Tasdemir, Unal; Ergun, Tulin; Direskeneli, Haner; Alibaz‐Oner, Fatma
Abstract: Objectives: Vascular involvement is one of the major causes of morbidity and mortality in Behçet's disease (BD) patients. Immunosuppressive (IS) agents are the mainstay of vascular BD (VBD) treatment; however, up to one‐third of patients relapse under conventional ISs. In this case series, we present the results of tumor necrosis factor‐alpha (TNFα) inhibitor use for the treatment of VBD patients who were refractory to conventional ISs and corticosteroids. Methods: This retrospective multicenter study included 27 refractory VBD patients treated with TNFα inhibitor agents. All data were acquired from patient charts. Results: Complete clinical remission was achieved in 22 (80%) patients within 3 months of the initiation of TNFα inhibitors. Infliximab was the first choice of TNFα inhibitor in 24 and adalimumab in three patients. The median daily dose of corticosteroids significantly decreased at 3 months. A trend toward a higher rate of complete remission was observed with concomitant IS use compared to monotherapy of TNFα inhibitors (93% vs 67%, P = .09). Serious side effects were observed in two patients (one pneumonia and one tuberculosis). Conclusion: Tumor necrosis factor‐alpha inhibitors seem a highly effective option for remission‐induction of refractory VBD with an acceptable safety data. Concomitant IS use may achieve higher complete remission rates as compared to TNFα inhibitor monotherapy. Comparative efficacy and safety of biological agents for VBD require further prospective, randomized controlled studies with a longer duration of follow‐up.